Newman’s Error Analysis on Students’ Solving Numerical Problems Ability - Anggara, Benny; Solahudin, Iman (Universitas Islam Negeri Sunan Kudus, 2022)
It is necessary to have a suitable method in revealing students' ability to understand the concept of numbers, because it is the basis for understanding other mathematical concepts. Several errors in understanding the concept of numbers have been proven to produce mathematical learning difficulties for students. Newman’s Errors Analysis (NEA) is one of the effective methods in revealing how the students' achievement in understanding the concept of numbers. Therefore, this research was conducted to see mathematical abilities when students solve numerical problems based on Newman’s Errors Analysis (NEA). This research method is descriptive qualitative research having a number of research subject of five grade VII SMP students. The results obtained from this research the most students had errors on comprehension, meanwhile reading was not as fatal error. There were not big mistakes and only small errors on transformation, process skills, and encoding, Comprehension errors occurred as the result of the students’ ability in reasoning was not good enough. Therefore, they failed to relate the concept of numbers to other mathematical concepts. In general, students' mathematical ability in the concept of numbers was quite good because the errors occur are were still in the low category. However, some basic errors were still exists resulting new problems in learning process. Mathematics learning improvement could be done through several things, one of them is through the analysis of students' learning difficulties on the number’s concepts. Perlu adanya metode dalam mengungkap kemampuan siswa dalam memahami konsep bilangan, karena konsep bilangan merupakan basis dalam memahami konsep matematika lainnya. Beberapa kesalahan dalam memahami konsep bilangan terbukti menghasilkan adanya kesulitan belajar matematis bagi siswa. Newman’s Errors Analysis (NEA) adalah salah satu metoda yang efektif dalam mengungkap bagaimana ketercapaian siswa dalam memahami konsep bilangan sehingga pada penelitian ini dilakukan untuk melihat kemampuan matematika berdasarkan Newman’s Errors Analysis (NEA) pada saat siswa menyelesaikan masalah-masalah bilangan. Metode penelitian ini menggunakan pendekatan deskriptif kualitatif dengan subjek penelitian sebanyak 5 siswa kelas VII SMP. Hasil yang diperoleh dari penelitian ini adalah siswa mengalami kesalahan terbesar pada comprehension, sedangkan reading errors tidak menjadi kesalahan yang fatal bagi siswa. Pada transformation, process skills, dan encoding tidak terjadi kesalahan yang besar meskipun masih terdapat kesalahan. Kesalahan comprehension terjadi akibat kemampuan siswa dalam bernalar yang masih belum begitu baik, sehingga gagal dalam mengaitkan konsep bilangan dengan konsep matematika lainnya. Secara umum, kemampuan matematika siswa dalam konsep bilangan sudah cukup baik karena kesalahan yang terjadi masih pada kategori kecil. Namun, masih terjadi beberapa kesalahan yang dasar sehingga akan mengakibatkan adanya masalah baru dalam pembelajaran. Perbaikan pembelajaran matematika dapat dilakukan melalui beberapa hal yang salah satunya adalah melalui analisis kesulitan belajar siswa pada konsep bilangan.